Kedinamikan kecinaan dan identiti orang Cina di Malaysia - Lee, Yok Fee (Universiti Kebangsaan Malaysia, 2004)
Since achieving its independence, Malaysia hitherto faces challenges in reaching unity and national integration among its people mainly due to its pluralistic background. The effectiveness of the government policies in building a nation-state is heavily contingent upon the understanding and interpretation of each ethnic group’s identity. Thus, this paper is trying to provide an understanding of the nature of the Chinese identity and Chineseness. By using interactionism theory, I try to present an analysis on the dynamics of Chinese identity when the Chinese are in the different societal environment, i.e. from China to Malaysia